Is ‘Social Cooperation’ for traditional irrigation, while ‘Technology’ is for motor pump irrigation? - Dessalegn, Mengistu; Merrey, Douglas J. (International Water Management Institute, 2014)
Based on a case study in Ethiopia, this paper shows that while farmers understand the social nature of community-managed irrigation, they share a narrow understanding of pump irrigation with policymakers as being primarily ‘technical’. They perceive pumps as liberating them from the ‘social’ limitations of traditional communal irrigation. However, the rapid expansion of pump irrigation is leading to increasing competition and conflict over limited water resources. We analyze the wider implications for Africa of this lack of visibility of the social dimension of pump irrigation, and offer suggestions for future policy and applied research to address the problem before it becomes a widespread crisis.